Occupiers' Liability in the Retail Industry - Sadler, Pauline (2002)
When a customer is injured on the premises of a retailer, the retailer may be liable for damages. The cause of action is 'occupiers'liability', which since Australian Safeway Stores v Zaluzna (1987) 162 CLR 479 has been incorporated into the ordinary principles of negligence. This article examines the liability of retailers in the tort of negligence, with particular reference to the required standard of care. The Wrongs Act 1958 (Vic), Occupiers Liability Act 1985 (WA), and Wrongs Act 1936 (SA) are included in the discussion. Cases referred to include Wheat v Lacon [1966] AC 552, Rose v Abbey Orchard Property Investments Pty Ltd (1987) Aust Torts Reports 80-121, Drakos v Woolworths (SA) Ltd (1991) Aust Torts Reports 81-135, Kocis v SE Dickens Pty Ltd (t/as Coles New World Supermarket) (1996) Aust Torts Reports 81-382, Kelly v Lend Lease Retail (1993) Aust Torts Reports 81-216, Griffin v Coles Myer Ltd (1991) Aust Torts Reports 81109, Razic v Cruz [2000] NSWCA 66 and Daily v Spot-On Investments Pty Ltd t/as Spot-On Photos (1995) Aust Torts Reports 81-365.